2015
DOI: 10.1016/j.bmc.2015.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Novel 4-substituted-N,N-dimethyltetrahydronaphthalen-2-amines: synthesis, affinity, and in silico docking studies at serotonin 5-HT2-type and histamine H1 G protein-coupled receptors

Abstract: Syntheses were undertaken of derivatives of (2S, 4R)-(−)-trans-4-phenyl-N,N-dimethyl-1,2,3,4-tetrahydronaphthalen-2-amine (4-phenyl-2-dimethylaminotetralin, PAT), a stereospecific agonist at the serotonin 5-HT2C G protein-coupled receptor (GPCR), with inverse agonist activity at 5-HT2A and 5-HT2B GPCRs. Molecular changes were made at the PAT C(4)-position, while preserving N, N-dimethyl substitution at the 2-position as well as trans-stereochemistry, structural features previously shown to be optimal for 5-HT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 34 publications
0
21
2
Order By: Relevance
“…To efficiently produce novel 4‐PAT derivatives, we designed and implemented an improved synthetic route compared to an earlier report (Sakhuja et al, 2015). Previously, we synthesized key compounds like 2a using a four‐step procedure from commercially available 3‐bromostyrene and trifluoroacetyl phenylacetyl anhydride (Canal et al, 2014; Sakhuja et al, 2015). The overall yield for this pathway, however was low and reproducibility in large scale was unreliable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To efficiently produce novel 4‐PAT derivatives, we designed and implemented an improved synthetic route compared to an earlier report (Sakhuja et al, 2015). Previously, we synthesized key compounds like 2a using a four‐step procedure from commercially available 3‐bromostyrene and trifluoroacetyl phenylacetyl anhydride (Canal et al, 2014; Sakhuja et al, 2015). The overall yield for this pathway, however was low and reproducibility in large scale was unreliable.…”
Section: Resultsmentioning
confidence: 99%
“…However, (2 S ,4 R )‐ 1 binds to H 1 receptors with high affinity and to 5‐HT 2 ‐type receptors with only moderate affinity. Bromine substitution at the meta ‐position of 4‐PAT ring C yielded (2 S ,4 R )‐ 2a (Figure 1), a ligand with lower affinity at H 1 receptors, higher affinity at 5‐HT 2 ‐type receptors (Canal et al, 2014; Sakhuja et al, 2015), yet no subtype selectivity. Notably, (2 S ,4 R )‐ 2a demonstrated antipsychotic‐like activity in several mouse models (Canal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 H]Myo–inositol (specific activity 22.5 Ci/mmol) was purchased from PerkinElmer Life and Analytical Sciences (Waltham, MA). The 5-HT 2C receptor agonists PAT (Booth et al, 2009) and its meta –bromophenyl substituted analog, MBP (Canal et al, 2014), as well as, the 5-HT 2C receptor inverse agonists MFP (Liu et al, 2017), and CAT (Sakhuja et al, 2015) were synthesized in our laboratory; free bases were converted to hydrochloride salts (Booth et al, 2009). The novel aminotetralin derivatives were > 99% pure, according to high–resolution mass spectrum, 1 H and 13 C nuclear magnetic resonance, and high performance liquid chromatography data (Sakhuja et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…5-HT 2C receptor inverse agonists assessed (Fig. 2) included the diazepine clozapine, the ergoline mesulergine, the benzo-dipyrrole SB 206553, and 2-aminotetralins (2 S ,4 R )-(−)- trans- 4-cyclohexyl- N , N -dimethyl-1,2,3,4-tetrahydronaphthalen-2-amine (4-cyclohexyl-2-dimethylaminotetralin, CAT), (2 S ,4 R )-(−)- trans- 4-(3’[ meta ]-trifluoromethylphenyl)- N , N -dimethyl-1,2,3,4-tetrahydronaphthalene-2-amine ( meta –trifluoro-PAT, MFP) (Sakhuja et al, 2015; Liu et al, 2017). We assessed both canonical Gα q signaling (via production of IP) and β-arrestin recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the conformation of this residue within the binding pocket impacts activation or inactivation of the receptor. 61,62 As the substituent at the As is the case with many chiral compounds 64 , including our lab's related 4-substititued-2-aminotetralin series 65 , one isomer can have higher affinity than another isomer(s) at the same GPCR. Thus, the chiral 5-SATs were separated by preparative chiral HPLC methods …”
Section: Literature Summary and Conclusionmentioning
confidence: 99%